Correlations among hope, fertility quality of life and negative emotions for couples undergoing their first in vitro fertilization–embryo transfer: a cross-sectional analysis - Hui Ye; Jing Zhao; Yujie Zou; Xiaorun Song; Mi Xu; Yu Zhang; Lili Zhang; Gaohua Wang (Reproductive Health)
Abstract Background The global incidence of infertility is increasing, and infertility has become an important medical and social issue. With the widespread application of in vitro fertilization-embryo transfer (IVF-ET) technology, the mental health problems of patients undergoing this treatment have gradually attracted widespread attention. The purpose of this study was to explore the relationships among the level of hope, the fertility quality of life and negative emotions of patients who underwent IVF-ET treatment for the first time to provide a scientific basis for subsequent psychological support interventions. Methods This study was a cross-sectional survey conducted at the Reproductive Medicine Center of Renmin Hospital of Wuhan University. From February 2023 to October 2023, 1425 patients who received IVF-ET treatment for the first time participated in the questionnaire survey. The survey content included the General Information Questionnaire, the Fertility Quality of Life (FertiQoL) Questionnaire, and the Herth Hope Index (HHI). Pearson correlation analysis was used to examine the relationships among the level of hope, fertility quality of life, and negative emotions. Results The survey included 805 women and 620 men representing 603 couples. The level of hope in patients undergoing IVF-ET treatment for the first time was positively correlated with fertility quality of life (r = 0.247, P < 0.01), and the level of hope was negatively correlated with negative emotions (stress: r = − 0.135, P < 0.01; anxiety: r = − 0.105, P < 0.01; depression: r = − 0.189, P < 0.01). Fertility quality of life was negatively correlated with negative emotions (stress: r = − 0.609, P < 0.01; anxiety: r = − 0.533, P < 0.01; depression: r = − 0.591, P < 0.01). Among couples undergoing IVF-ET treatment for the first time, the husband’s level of hope (r = 0.131, P < 0.01), fertility quality of life (r = 0.372, P < 0.01), and negative emotions (stress: r = 0.181, P < 0.01; anxiety: r = 0.163, P < 0.01; depression: r = 0.210, P < 0.01) were positively correlated with those of his wife. Conclusions In patients undergoing their first IVF-ET treatment, there is a significant correlation among hope, fertility quality of life, and negative emotions. Moreover, within couples, the levels of hope, fertility quality of life, and negative emotions of husbands and wives mutually influence each other. Enhancing the level of hope in this population is conducive to alleviating negative emotions and improving their fertility quality of life. The mutual influence of spouses should not be overlooked in clinical practice, and psychological support for both partners should be emphasized.